The Use of Multimodal Discourse Analysis to Study the Relationship Between Visual, Lingual, and Written Text of Artificial Intelligence in TED (Technology, Entertainment, and Design) Talks YouTube Channel - Hadriyan, Ferry; Mujiyanto, Januarius Mujiyanto; Rukmini, Dwi (English education journal, 2022)
This study was aimed to discover the types of processes used Multimodal Discourse Analysis (MDA) to study the relationship between Visual, Lingual, and Written text, and how they influence the authors to analyze of Artificial Intelligence Video’ Alexandr Wang speech in TED (Technology, Entertainment, and Design) talks YouTube channel. Artificial intelligence is a set of sciences, theories, and techniques whose purpose is to reproduce by a machine the cognitive abilities of a human being. Machine-based systems can give a set of human-defined objectives and make predictions, recommendations, or decisions that influence real or virtual environments. AI systems interact with us and act on our environment directly or indirectly. Often, they appear to operate autonomously and can adapt their behavior by learning about the context, (UNICEF 2021: 16). AI systems are algorithmic models that carry out cognitive or perceptual functions in the world that were previously reserved for thinking, judging, and reasoning human beings. (Leslie et al. 2021: 8). MDA is a term that is used to refer to the way people communicate using different modes at the same time (Kress & van Leeuwen, 1996), which is defined as the use of several semiotic methods in product design, or semiotic events simultaneously, and in a certain way these modes combined with strengthening, compliment, or be in a certain arrangement (Kress and van Leeuwen, 2001).